Cytomegalovirus transmission from breast milk in premature babies: does it matter?. Issue 2 (1st September 2002) - Bryant, P; Morley, C; Garland, S; Curtis, N
Abstract : There is evidence that CMV is commonly present in breast milk and is often transmitted to babies. CMV infection acquired postnatally can cause serious disease in very premature babies. Interventions to remove CMV from breast milk are possible but may damage other important constituents.